2018
DOI: 10.31196/huvfd.508807
|View full text |Cite
|
Sign up to set email alerts
|

Kangal Köpeklerinde Trachea’nın Bilgisayarlı Tomografi ile Üç Boyutlu Değerlendirilmesi

Abstract: Bu araştırma; Kangal köpeklerinde ilk kez bilgisayarlı tomografik görüntüler kullanılarak trachea'nın ayrıntılı anatomisini elde etmek amacıyla gerçekleştirilmiştir. Çalışmada 5 erkek ve 5 dişi olmak üzere toplam 10 erişkin Kangal köpeği kullanılmıştır. Multidedektör bilgisayarlı tomografi (MDBT) cihazından elde edilen görüntüler, üç boyutlu (3D) modelleme yazılımı (VITAL, Vitrea 2,HP XW 6400) ile trachea'nın üç boyutlu yeniden yapılandırılmasında kullanılmıştır. Trachea'nın ölçümleri; hem pars cervicalis hem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In the literature, there are studies in which pelvis measurements were made in terms of sex for different species. In studies, it was reported that the diameter of pelvic cavity were higher in males than females in kangal dog (Atalar et al, 2017), gazelle (Demircioglu, Yilmaz, et al, 2021) and New Zealand Rabbit (Özkadif et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there are studies in which pelvis measurements were made in terms of sex for different species. In studies, it was reported that the diameter of pelvic cavity were higher in males than females in kangal dog (Atalar et al, 2017), gazelle (Demircioglu, Yilmaz, et al, 2021) and New Zealand Rabbit (Özkadif et al, 2014).…”
Section: Introductionmentioning
confidence: 99%